THE EFFECT OF HYPERBARIC OXYGEN THERAPY IN TREATING FOR IRRADIATED HEAD AND NECK CANCER PATIENTS: A SYSTEMATIC REVIEW (Vietnam Journal of Community Medicine, 2022)
Objectives: To summarize the effectiveness of hyperbaric oxygen therapy in the treatment of patientswho underwent radiation therapy for head and neck cancer from 1992 to 2022.Subjects and methods: This systematic review uses the open data sources Pubmed, Google Scholarto search for articles and full-text researches written in English in accordance with the selectioncriteria.Results: The number of articles selected and included in the systematic review was 21. The resultsshow that hyperbaric oxygen therapy is effective in reducing xerostomia, however, its effectivenessin reducing risk/accelerating healing process of osteoradionecrosis and improving patients’ qualityof life has not been agreed.Conclusion: More well-designed randomized controlled trials with uniform protocols are needed torecommend the use of hyperbaric oxygen therapy for irradiated head and neck cancer patients.
Keywords: Hyperbaric oxygen, head and neck cancer, radiation therapy, systematic review